Avaliação comparativa do desempenho de alunos admitidos na Faculdade de Odontologia da Universidade Federal de Uberlândia - FOUFU - via Vestibular e via PAIES, no período de 2000/1 a 2003/2 - Reis, Simone Maria de ávila Silva (2006)
The research approached the selective process used by the Brazilian Colleges in the admission of candidates to the higher education. The raising demand for vacancies in the public universities contributed to the exceeding competition in the college entrance exams, what rebounded in the way of high school conduction, that has acquired propaedeutic characteristics. The negative reflection about the objectives of this level of the teaching trigged off searches for the alternatives selective process, that could rescue and encourage the realization of the purposes originally offered to the high school. New proposals acquired impulse with the promulgation of the Lei de Diretrizes e Bases da Educação Nacional (LDB) nº 9394, in 12/20/1996, that extinguished the traditional college entrance exams exclusiveness as the selection s way. The Universidade Federal de Uberlândia implanted the Alternative Process to College Entrance PAIES, a process of evaluation in series, with exams aplicated in the end of the three series of high school. The candidates that reach the best general results in the three evaluations, since 1997, are selected to occupy 25% of the offered vacancies, yearly, by the higher courses of UFU; entering always in the first semester. While the traditional college entrance exams selects for the others 75% of the offered vacancies; that enter in both semesters. The aim of this work was to know the factor of predictive validate of these two selective processes, through the comparison of the academic performance of the student s groups of the Faculdade de Odontologia da Universidade Federal de Uberlândia (FOUFU) admitted by traditional college entrance exams and by Alternative Process to College Entrance (PAIES). The subjects of the research were the students of the 51º to 56º groups of the Odontology Course, examined in pre established periods of the course, by analysis of the official registers of notes and subjective evaluation of the students and the teachers, by the application of the questionnaire. The data, collected between 2002/2 and 2003/2, were treated statistically and analyzed qualitatively and quantitatively. The results allowed to conclude that the admitted students by Alternative Process to College Entrance (PAIES) presented best academic performance and best competence of learning during the graduation, and suggested that this selective process present level of factor of predictive validate higher then the traditional college entrance exams.